PENYULUHAN ANEMIA PADA REMAJA PUTRI DI DESA BARO YAMAN KECAMATAN MUTIARA KABUPATEN PIDIE - Salamah Salamah; Zaitun Zaitun; Amelia Faris (COVIT (Community Service of Health), 2021)
Adolescent girls are the phase where the peak of growth occurs and the onset of menstruation which is related to the high need for iron. However, a lack of health knowledge and poor eating habits result in a lack of nutritious food intake and a risk of developing anemia. Young women as future mothers are the starting point for investment in nutrition for the First 1000 Days of Life. Malnourished pregnant women will give birth to babies with sub-optimal nutritional status and are at great risk of reducing their intelligence potential at school age and their productivity at adulthood. Thus, equipping young women with good knowledge about nutrition and health is very important. Good knowledge is expected to equip them to practice good nutrition and health. The purpose of this community service is to provide knowledge about anemia and adherence of young women in taking iron tablets. This service method uses counseling (lectures and questions and answers) about Anemia and the adherence of young women in taking iron tablets. Conclusion: Young women are able to understand the prevention of anemia in adolescents. It is suggested to health workers, especially the Puskesmas, to provide counseling about anemia to young women more often before giving iron tablets, so that students get information about anemia and want to consume blood tablets given. Keywords: Counseling, Anemia, Young Women